PROGRESSIVE METHODS OF ASSESSING THE CAPITAL VALUE OF JOINT STOCK COMPANIES IN DEVELOPED COUNTRIES - Khurshid Kgudoykulov (International Journal of Business, Law and Political Science, 2024)
The article examines and analyzes the scientific and practical aspects of progressive methods for estimating the cost of capital of joint-stock companies in developed countries. It also describes methods commonly used in world practice, including methods of cost of equity and weighted average cost of capital. In addition to this , the methods used to analyze the cost of capital of joint-stock companies in Europe and the United States. In particular, the progressive capital valuation was used by the four largest accounting and consulting firms in the world.